Operational and economic design of multi-terminal medium DC voltage hybrid renewable energy systems for effective power sharing - M. M., Ahmed; F. C., Jong; Lau Wei, Kin; Ahmed Mohamed, Ahmed Haidar (Elsevier B.V., 2025)
The advancement of multi-terminal medium-voltage direct current (MVDC) technology is accelerating the transition of DC distribution from point-to-point connections to renewable integrated systems. However, the integration of remote renewable sources introduces challenges in control and economic optimization, particularly for voltage-source converter (VSC)-based designs. Therefore, this paper proposes a multi-terminal MVDC architecture for hybrid renewable energy systems with three primary objectives: to develop an effective power-sharing control using a modular multilevel converter-based topology, to assess the economic feasibility of hybrid configurations under varying load and weather conditions, and to implement real-time monitoring through an Internet of Things-based cloud platform. The scope of this paper encompasses the development and validation of decentralized droop control for reliable power sharing, techno-economic analysis using the hybrid optimization of multiple energy resources (HOMER) for cost and energy optimization, real-time system monitoring through ThingSpeak, and MATLAB-based Internet of Things (IoT) integration. Additionally, it includes transient fault simulations to evaluate voltage stability and system resilience. A generalized framework that combines decentralized droop control and economic optimization is established for system sizing and operational reliability assessment. Simulation results indicate that the proposed system maintains DC voltage deviations within 3 % under steady-state conditions, 3.1 % following AC three-phase faults, and as low as 2.2 % after DC pole-to-pole short-circuit events. The unmet load percentage was extremely low (0.0165 %), while excess energy remained manageable (up to 8 %). The system achieves a levelized cost of energy (LCOE) of 0.4114 $/kWh and a renewable energy share of up to 44 %. These results demonstrate that the proposed MVDC configuration is technically robust, cost-effective, and IoT-enabled, making it well-suited for renewable energy integration in Sarawak, Malaysia.